2016
DOI: 10.1111/evo.12852
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal environmental heterogeneity and the maintenance of the tailspot polymorphism in the variable platyfish (Xiphophorus variatus)

Abstract: Genetic variation is critical for adaptive evolution. Despite its importance, there is still limited evidence in support of some prominent theoretical models explaining the maintenance of genetic polymorphism within populations. We examined 84 populations of Xiphophorus variatus, a livebearing fish with a genetic polymorphism associated with physiological performance, to test: (1) whether niche differentiation explains broad-scale maintenance of polymorphism, (2) whether polymorphism is maintained among popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
(158 reference statements)
0
7
0
Order By: Relevance
“…; Culumber et al. ; Gulisija and Kim ; Culumber and Tobler ), there is little understanding of how variation in the social environment—and particularly the genetic composition of the social environment—can influence the maintenance of variation (Saltz and Nuzhdin ). Phenotypic differences caused by genetic variation in the social environment are generally termed "indirect genetic effects" (IGEs: Moore et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Culumber et al. ; Gulisija and Kim ; Culumber and Tobler ), there is little understanding of how variation in the social environment—and particularly the genetic composition of the social environment—can influence the maintenance of variation (Saltz and Nuzhdin ). Phenotypic differences caused by genetic variation in the social environment are generally termed "indirect genetic effects" (IGEs: Moore et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of theoretical and empirical studies have suggested that spatially or temporally fluctuating selection can maintain adaptive genetic variation (Levene 1953;Gillespie and Turelli 1989;Huang et al 2014;Culumber et al 2015;Gulisija and Kim 2015;Culumber and Tobler 2016), there is little understanding of how variation in the social environment-and particularly the genetic composition of the social environment-can influence the maintenance of variation (Saltz and Nuzhdin 2014). Phenotypic differences caused by genetic variation in the social environment are generally termed "indirect genetic effects" (IGEs: Moore et al 1997;Wolf et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Wigg (Vavrek, McGraw, & Yang, 1996), while annually varying moisture conditions in a desert may conserve flower color polymorphism in the annual Linanthus parryae (A.Gray) Greene (Schemske & Bierzychudek, 2001). In the fish Xiphophorus variatus, the level of temperature variability within days and years has been found to be positively associated with withinpopulation diversity in tail spot richness (Culumber & Tobler, 2016), with the fitness rank of different spot types depending for instance on the thermal environment (Culumber, Schumer, Monks, & Tobler, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Population genetic theory indicates that environmental heterogeneity can maintain additive quantitative genetic variation [21][22][23], a result supported by some of the few empirical studies on the topic [24][25][26][27][28], but not by others (e.g. [29]).…”
Section: Introductionmentioning
confidence: 99%